BANK UMUM INDONESIA DAN MASALAH NILAI TUKAR VALUTA ASING - A Baidhawi (Universitas Batanghari Jambi, 2010)
The effect of exchange rate changing is very much influenced the several National Bank in Indonesia especially devisa Banking. It relationship with the choices of strategies high risk and also the possibility to gain high income. Study of environmental, strategy and performance try to include exchange rate as one of environmental factor, which act as exogen variable. Theories needed to support are foreign currency exchange, exchange rate changing and implication of them, so does possible anticapation.Keyword : Exchange Rate, Foreign Exchange